A STUDY ON REGISTER USED IN LIVE TEXT COMMENTARY ON EURO 2012 FINAL FOOTBALL MATCH “SPAIN VS ITALY” - CANDRA, MUHAMMAD ADI (Jurnal Ilmiah Mahasiswa FIB, 2013)
People as social humans need a language to communicate with others.They need it since language is a device for communication. In society, language isremarkably varied. One of the varieties of language is register. Register is alanguage used in particular field, profession, and situation. The language offootball commentary, pimp, and radio broadcaster are considered as examples ofregister language. The study of register can be conducted from many aspects suchas, the vocabulary, syntactic features, phonology characteristics, register variable,etc. In this study, the researcher conducted the register used in live text footballcommentary on Euro 2012 final football match between Spain and Italy. There arethree problems of the study which were proposed: (1) What the registers are usedin live text commentary, (2) What the meanings of registers are used in live textcommentary, (3) What the linguistic features of register are used in live textcommentary on Euro 2012 final football match between Spain and Italy.  This study used qualitative approach in relation to the use of clear andsystematic description about the phenomena being studied. The data were onlytaken from live text commentaries which were uploaded on BBC sport website.  This study revealed that the registers used in live text commentarycommonly have different meaning when it relates to other field, profession andsituation. Some registers are unfamiliar words which do not exist in other fieldoutside the football. This study also revealed that live text football commentaryusually uses features such as, syntactic reduction and passive voice. From bothfeatures, the commentator uses the syntactic reduction more frequently. Thereduction and passive voice are not due to the insufficient competence of thecommentator. Nevertheless, there are some reasons behind such as, to build extraspeed in delivering the event. The researcher suggests the English Department students conduct thedeeper study about register since this study did not cover all aspects of registeryet. He also hopes that the next researcher will conduct the comparison studyabout register used in live text commentary with that used in live oralcommentary. Keywords: Sociolinguistics, Register, Live text commentary